Development of an Adaptive Wall-pressing Mechanism for an In-pipe Cleaning Robot. Issue 1 (1st November 2022) - Yang, Zeyu; Fan, Yuanxun; Yan, Yu
Abstract: This paper proposes a novel adaptive wall-pressing mechanism for an in-pipe cleaning robot (ICR) which combines two type of self-adaptive mechanisms. Parametric modelling and optimization for the mechanism is proceeded in order to improve the carrying capacity and adaptability of the robot in the water supply pipeline. Force in the compression spring due to the self-weight of ICR is reduced by 31% after optimization. A virtual simulation platform is established to analyse the stability and obstacle-surmounting capacity of ICR under different pre-loading forces.